EFL pre-university students' readiness for learner autonomy: Does culture matter? - Abdul Malik, Faridah; Mohd. Asraf, Ratnawati; Othman, Khairiah; Muhamad, Ainon Jariah (English Language Education Publishing, 2017)
Language learning is a lifelong endeavor. Learners have to work within and beyond the classroom to develop their language skills. Hence, enhancing learners’ autonomy has become a key concern for language teachers as it is seen as a means to help learners in directing their own learning process. However, its relevance is sometimes questioned, as it is perceived to be a Western concept, not appropriate for contexts such as those in Asia, which have different educational traditions. This paper discusses the results of a study that was aimed at assessing pre-university students’ readiness for learners autonomy in language learning and the extent to which their perceptions differ according to their educational background and culture. The findings provide some insights into how culture can influence students’ beliefs and practices about taking charge of their own language learning.